The Geological speed of sedimentation - Гриценко, В. (Київський національний університет імені Тараса Шевченка, 2006)
The article deals with examine of speed of sedimentation in West Ukrainian paleobasins. We must understand that geological speed of sedimentation is result of interaction of coalescent processes. The comparison rank of sedimentary rocks shows slowly decreasing sequence from Rifean to Lower Devonian in observed basins. Consequently, we get objective result that tectonic activity there was reduced.

Йдеться про висновки, які випливають з дослідження геологічної швидкості накопичення осадових утворень у рифейских, вендських і ранньопалеозойсьаких басейнах заходу України. Результати свідчать про суттєве зменшення геологічної швидкості осадконагромадження, що може бути підтвердженням тези про послаблення тектонічної активності із плином часу.
Геологічна швидкість осадконагромадження